Effect of Addition Virgin Coconut Oil (VCO) on Physical Stability and SPF Value of Sunscreen Cream Combination of Zinc Oxide and Titanium Dioxide - Jayati, Bella Corry; Annisa, Rahmi; Firdausy, Alif Firman; Megawati, Dewi Sinta; Fauziyah, Begum (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2021)
Virgin Coconut Oil (VCO) is one of the natural ingredients used as antioxidants because of the high saturated fatty acids that cause VCO to be resistant to oxidation. In this research, a combination of zinc oxide (ZnO) and titanium dioxide (TiO2) sunscreen cream formulation was carried out with the addition of VCO as an antioxidant. The purpose of this study was to determine the effect of adding VCO to physical stability and SPF values ​​of sunscreen cream combination of zinc oxide (ZnO) and titanium dioxide (TiO2). Sunscreen cream made 5 formulas, namely F1 (7% VCO), F2 (8% VCO), F3 (ZnO + TiO2), F4 (ZnO + TiO2 + VCO 7%) and F5 (ZnO + TiO2 + VCO 8%). The results showed that sunscreen cream formulas 1,2,4, and 5 had good physical-chemical characteristics and were stable during the storage period. While formula 3 produces white cast and is unstable in storage with temperature changes. The formula for sunscreen cream that produces the best SPF value is F5 (ZnO + TiO2 + VCO 8%) with the ultra protection type.